Republic of Tajikistan : Poverty Assessment - World Bank (Washington, DC, 2013)
Poverty is the central development issue in Tajikistan. The country is now one of the poorest in the world. It was made worse by the civil conflict in the early 1990s. This report suggests that there should be four key pillars to a poverty reduction program strategy: a) the stimulation of high labor productivity and economic growth; b) the provision of basic social services; c) the targeting of assistance to the poorest; and d) the development of a well-governed and safe environment. The report recommends the following: 1) further analysis should be undertaken of the incidence of public spending, to ensure that key programs are adequately funded and that spending contributes as much as possible to poverty reduction. 2) The Government should set specific targets for welfare indicators and poverty reduction. 3) A list should be compiled of possible projects of a targeted program of interventions that could impact rapidly on poverty; the projects should be fully costed and implementation arrangements studied. 4) Alternative funding sources, including the Government's own budget and external donors, should be explored for the financing of the list of possible targeted interventions.